IMPLEMENTASI KEBIJAKAN ANALISIS JABATAN DAN ANALISIS BEBAN KERJA PADA DINAS KEBUDAYAAN PROVINSI SULAWESI TENGAH - Fahry Aprial Mahmud; Nuraisyah; Suasa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Fahry Aprial Mahmud, STAMBUK : B 101 22 008, This thesis describes the results of research on the Implementation of the Policy of the Minister of Apparatus Empowerment and Bureaucratic Reform concerning Guidelines for Position Analysis and Workload Analysis at the Cultural Office of Central Sulawesi Province. guided by Nuraisyah and Suasa This study aims to determine how the Implementation of the Policy of the Minister of Apparatus Empowerment and Bureaucratic Reform concerning Guidelines for Position Analysis and Workload Analysis at the Cultural Office of Central Sulawesi Province. In this study researchers used the theory of Edward III (2005: 126) which consists of criteria for Communication, Resources, Disposition, and Bureaucratic Structure. The research method used is a qualitative descriptive research type. Data collection was carried out using observation, documentation, and interview methods. The determination and number of informants in this study used purposive sampling techniques, namely the parties who Considered to know in depth various things regarding research problems totaling 5 (five) people. While data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing / verification. Based on the results of this study, it can be concluded that there are several problems that need special attention, namely there are still discrepancies in the placement of civil servants based on the results of position analysis and workload analysis that have been prepared by regional officials, besides that the number of civil servants in the Cultural Office is very small so that the arrangement and planning carried out are not effective and efficient.